Sintesis Kulit Telur Ayam/Serbuk Besi Menjadi Katalis Cao/Serbuk Besi Untuk Reaksi Transesterifikasi Minyak Sawit Off Grade Menjadi Biodiesel - Gusti Ayu Nurjanah; Zuchra Helwani; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Heterogeneous solid base catalyst by modificated Eggshells through calcination, hydration, dehydration methods with iron powder through impregnation method to load calcium oxide with eggshells as precursor. The catalyst with the highest activity is obtained when the calcination temperature of 900°C and the calcination time of 2 hours under transesterification reaction conditions of a molar ratio of methanol/oil 10:1, catalyst dosage of 1% by weight, temperature of 70 °C for 2 hours with yield biodiesel results reached 91,72%.Keyword: biodiesel, calcination, calcium oxide, catalysts, iron powder.